Does chest mobilization affect trunk control and balance in children with spastic cerebral palsy - Kavita; Gupta, Aarti; Kumar, Saurabh (International Journal of Research in Medical Sciences, 2025)
Background: Chest mobility has been reported to be reduced in children with spastic cerebral palsy (CP). This study was conducted to determine the effectiveness of chest wall mobilisation on trunk control and balance in children with CP. Methods: The 32 children who participated in this single-blind trial were divided into two groups at random. Group A (n=16) received conventional intervention and chest mobilisation, while group B (n=16) received only conventional intervention. For a period of six weeks, the intervention was carried out three days a week. After six weeks of therapy, participants were reassessed using the paediatric berg balance scale (PBS) for evaluating balance and the trunk control measurement scale (TCMS) for evaluating trunk control. Results: The Wilcoxon test was used to assess differences within the group, while the Mann Whitney ’U’ test was used to determine whether there were any differences between the two groups. The pre- and post-treatment scores of the variables TCMS and PBS were used to illustrate the results as a mean and standard deviation. Comparison of each group’s outcome metrics before treatment revealed no significant differences. While, comparing the results of chest mobilisation with conventional physiotherapy in group A showed a notable improvement in the ability to maintain balance and trunk control (p<0.05) Conclusions: In children with CP, chest mobilisation has a positive effect and can be combined with conventional physiotherapy techniques to enhance balance and develop trunk control.